REGIONAL GOVERNMENT'S STRATEGY TO HANDLE THE IMPACT OF FREE ASSOCIATION IN THE EX-GEMPOL PORONG LOCALIZATION: STRATEGI PEMERINTAH DAERAH MENANGANI DAMPAK PERGAULAN BEBAS DI EKS LOKALISASI GEMPOL PORONG - Adiliya Putri; Yuli Kartika Efendi (SOSIOEDUKASI, 2023)
The objective of this study is to describe the strategy of Kaliploso village government in dealing with the impact of promiscuity in Gempol Porong localization area, Cluring District, Banyuwangi Regency. This research used a qualitative descriptive approach. Data collection techniques were conducted by interview, observation and documentation methods. The data analysis used is Miles and Huberman method. The analysis unit in this study is village government and youth. The results showed that Kaliploso village government's strategy by innovating through the village work program which held various activities to mobilize the youth to participate actively and productively in positive activities went quite well and significantly. The Kaliploso village government has also collaborated with several related parties as an effort to monitor and anticipate the activities carried out by teenagers. The village work programs implemented are 1) KHC (Kaliploso Horty Carnival), 2) Kaliploso Rijig, 3) The workshops of the drugs dangerous , 4) livestock assistance, and 5) Al-Qur'an Garden Agrotourism. In dealing with the impact of promiscuity in Gempol Porong localization area, this village program is also expected to change the image of the village become better.